1 [[!toc]]
3 #These notes return to the topic of fixed point combiantors for one more return to the topic of fixed point combinators#
5 Q: How do you know that every term in the untyped lambda calculus has
6 a fixed point?
8 A: That's easy: let `T` be an arbitrary term in the lambda calculus.  If
9 `T` has a fixed point, then there exists some `X` such that `X <~~>
10 TX` (that's what it means to *have* a fixed point).
12 <pre>
13 let W = \x.T(xx) in
14 let X = WW in
15 X = WW = (\x.T(xx))W = T(WW) = TX
16 </pre>
18 Please slow down and make sure that you understand what justified each
19 of the equalities in the last line.
21 Q: How do you know that for any term T, YT is a fixed point of T?
23 A: Note that in the proof given in the previous answer, we chose `T`
24 and then set `X = WW = (\x.T(xx))(\x.T(xx))`.  If we abstract over
25 `T`, we get the Y combinator, `\T.(\x.T(xx))(\x.T(xx))`.  No matter
26 what argument `T` we feed Y, it returns some `X` that is a fixed point
27 of `T`, by the reasoning in the previous answer.
29 Q: So if every term has a fixed point, even Y has fixed point.
31 A: Right:
33     let Y = \T.(\x.T(xx))(\x.T(xx)) in
34     Y Y = \T.(\x.T(xx))(\x.T(xx)) Y
35         = (\x.Y(xx))(\x.Y(xx))
36         = Y((\x.Y(xx))(\x.Y(xx)))
37         = Y(Y((\x.Y(xx))(\x.Y(xx))))
38         = Y(Y(Y(...(Y(YY))...)))
40 Q: Ouch!  Stop hurting my brain.
42 A: Let's come at it from the direction of arithmetic.  Recall that we
43 claimed that even `succ`---the function that added one to any
44 number---had a fixed point.  How could there be an X such that X = X+1?
45 Then
47     X = succ X = succ (succ X) = succ (succ (succ (X))) = succ (... (succ X)...)
49 In other words, the fixed point of `succ` is a term that is its own
50 successor.  Let's just check that `X = succ X`:
52     let succ = \n s z. s (n s z) in
53     let X = (\x.succ(xx))(\x.succ(xx)) in
54     succ X
55       = succ ((\x.succ(xx))(\x.succ(xx)))
56       = succ (succ ((\x.succ(xx))(\x.succ(xx))))
57       = succ (succ X)
59 You should see the close similarity with YY here.
61 Q. So `Y` applied to `succ` returns infinity!
63 A. Yes!  Let's see why it makes sense to think of `Y succ` as a Church
64 numeral:
66       [same definitions]
67       succ X
68       = (\n s z. s (n s z)) X
69       = \s z. s (X s z)
70       = succ (\s z. s (X s z)) ; using fixed-point reasoning
71       = \s z. s ([succ (\s z. s (X s z))] s z)
72       = \s z. s ([\s z. s ([succ (\s z. s (X s z))] s z)] s z)
73       = \s z. s (s (succ (\s z. s (X s z))))
75 So `succ X` looks like a numeral: it takes two arguments, `s` and `z`,
76 and returns a sequence of nested applications of `s`...
78 You should be able to prove that `add 2 (Y succ) <~~> Y succ`,
79 likewise for `mult`, `minus`, `pow`.  What happens if we try `minus (Y
80 succ)(Y succ)`?  What would you expect infinity minus infinity to be?
81 (Hint: choose your evaluation strategy so that you add two `s`s to the
82 first number for every `s` that you add to the second number.)
84 This is amazing, by the way: we're proving things about a term that
85 represents arithmetic infinity.  It's important to bear in mind the
86 simplest term in question is not infinite:
88      Y succ = (\f.(\x.f(xx))(\x.f(xx)))(\n s z. s (n s z))
90 The way that infinity enters into the picture is that this term has
91 no normal form: no matter how many times we perform beta reduction,
92 there will always be an opportunity for more beta reduction.  (Lather,
93 rinse, repeat!)
95 Q. That reminds me, what about [[evaluation order]]?
97 A. For a recursive function that has a well-behaved base case, such as
98 the factorial function, evaluation order is crucial.  In the following
99 computation, we will arrive at a normal form.  Watch for the moment at
100 which we have to make a choice about which beta reduction to perform
101 next: one choice leads to a normal form, the other choice leads to
102 endless reduction:
104     let prefac = \f n. isZero n 1 (mult n (f (pred n))) in
105     let fac = Y prefac in
106     fac 2
107        = [(\f.(\x.f(xx))(\x.f(xx))) prefac] 2
108        = [(\x.prefac(xx))(\x.prefac(xx))] 2
109        = [prefac((\x.prefac(xx))(\x.prefac(xx)))] 2
110        = [prefac(prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
111        = [(\f n. isZero n 1 (mult n (f (pred n))))
112           (prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
113        = [\n. isZero n 1 (mult n ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred n)))] 2
114        = isZero 2 1 (mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 2)))
115        = mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 1)
116        ...
117        = mult 2 (mult 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 0))
118        = mult 2 (mult 1 (isZero 0 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 0))))
119        = mult 2 (mult 1 1)
120        = mult 2 1
121        = 2
123 The crucial step is the third from the last.  We have our choice of
124 either evaluating the test `isZero 0 1 ...`, which evaluates to `1`,
125 or we can evaluate the `Y` pump, `(\x.prefac(xx))(\x.prefac(xx))`, to
126 produce another copy of `prefac`.  If we postpone evaluting the
127 `isZero` test, we'll pump out copy after copy of `prefac`, and never
128 realize that we've bottomed out in the recursion.  But if we adopt a
129 leftmost/call by name/normal order evaluation strategy, we'll always
130 start with the isZero predicate, and only produce a fresh copy of
131 `prefac` if we are forced to.
133 Q.  You claimed that the Ackerman function couldn't be implemented
134 using our primitive recursion techniques (such as the techniques that
135 allow us to define addition and multiplication).  But you haven't
136 shown that it is possible to define the Ackerman function using full
137 recursion.
139 A. OK:
141 <pre>
142 A(m,n) =
143     | when m == 0 -> n + 1
144     | else when n == 0 -> A(m-1,1)
145     | else -> A(m-1, A(m,n-1))
147 let A = Y (\A m n. isZero m (succ n) (isZero n (A (pred m) 1) (A (pred m) (A m (pred n))))) in
148 </pre>
150 For instance,
152     A 1 2
153     = A 0 (A 1 1)
154     = A 0 (A 0 (A 1 0))
155     = A 0 (A 0 (A 0 1))
156     = A 0 (A 0 2)
157     = A 0 3
158     = 4
160 A 1 x is to A 0 x as addition is to the successor function;
161 A 2 x is to A 1 x as multiplication is to addition;
162 A 3 x is to A 2 x as exponentiation is to multiplication---
163 so A 4 x is to A 3 x as super-exponentiation is to exponentiation...